Qualitative analysis of the integration effects and sense of belonging in the University: the case of ASEBio as the first organization of Bioengineering students - Neme, Claudia Alicia (2018)
The present article aims to reflect on the integration mechanisms of the student of bioengineering to university life. It is based on the thesis that socialization has repercussions on the students' sense of belonging and identity in relation to the career; which, in turn, affect academic well-being and performance. From there, the “Asociación Sanjuanina de Estudiantes de Bioingeniería" (ASEBio) is investigated, seeking to obtain feedback on the impact produced since its creation and, from there, to question its progress. In addition, it is intended as a model initiative for other groups of students to consider the option of creating university student associations. Thus, the creation of groups as direct and privileged way for the participation of the students in the direction of the construction of their identity is presented. They become thus facilitators of the welfare of the actors of the institution.